2004
DOI: 10.1080/10473289.2004.10470912
|View full text |Cite
|
Sign up to set email alerts
|

Source Characterization of Atmospheric Heavy Metals in Industrial/Residential Areas: A Case Study in Oman

Abstract: Total suspended particulate matter (TSP) was collected from two districts: the Sohar industrial estate (SIE) and a residential area in the case study area in Oman. The TSP collected from SIE was taken from 19 different industrial activities, whereas those collected from the residential area were taken from 12 houses. The samples were analyzed for nine heavy metals: chromium (Cr), copper (Cu), manganese (Mn), nickel, lead (Pb), zinc (Zn), cadmium, vanadium, and molybdenum. The results were used to assess the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…It is in accordance with the findings of other workers (Bakirdere and Yaman 2008;Abdul-Wahab 2004;Kakulu 2003). There was no considerable variation in the concentration among the selected samples; however, the highest value appeared at the sampling site S8, where Pb and Zn were also at maximum.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…It is in accordance with the findings of other workers (Bakirdere and Yaman 2008;Abdul-Wahab 2004;Kakulu 2003). There was no considerable variation in the concentration among the selected samples; however, the highest value appeared at the sampling site S8, where Pb and Zn were also at maximum.…”
Section: Resultssupporting
confidence: 95%
“…But it is still lower than some previous studies (Abdul-Wahab 2004;Kakulu 2003). The permissible limit of Pb in petrol is 0.02 g L −1 .…”
Section: Resultscontrasting
confidence: 58%
“…Correspondingly, OSI followed the same pattern as the TAC in the subgroup of auto technicians with the battery repairers having the highest OSI and following the same descending order as previously stated for TAC. Similar work [21, 22] showed that battery chargers were the most vulnerable to reduced TAC and increased OSI among the various subgroups of auto technicians studied. However, it is interesting to note that TPP was highest in panel beaters, the group with the lowest OSI among the subgroups.…”
Section: Discussionmentioning
confidence: 54%
“…The battery repairer is thus constantly exposed to the fumes in the course of his routine work which may have resulted in the observed elevated blood Pb levels in battery repairers in this study. In a similar work in Pakistan [21, 22], an increased exposure to lead by battery repairers among other auto technicians was also reported.…”
Section: Discussionmentioning
confidence: 78%
“…The candidate reference material presents a comparable composition with airborne PM samples (PM 10 and PM 2.5 ) [18,[34][35][36] and can therefore be defined as a suitable reference material for field campaigns of heavy metals analyses.…”
Section: Discussionmentioning
confidence: 99%